Recent advances and clinical implications of the micropapillary histological subtype in lung adenocarcinomas. (June 2014) - Lee, Ming-Ching; Buitrago, Daniel H; Kadota, Kyuichi; Jones, David R; Adusumilli, Prasad S
SUMMARY : Micropapillary (MIP) histologic subtype included in the classification of lung adenocarcinomas (ADCs) is associated with both size- and stage-independent poor prognoses. MIP pattern in lung ADCs, even at small, early stages, correlates with high lymphovascular invasion, visceral pleural invasion and lymph node metastases. Recently, we reported that patients with a MIP component are at a higher risk of locoregional recurrence after limited resection. Identification of a MIP pattern is only possible with permanent pathologic sections; preoperative imaging, cytology or intraoperative frozen section specimens remain unreliable. The intermixed, heterogenous morphology of lung ADC presents a technical challenge in investigating the molecular biology of cells with MIP morphology. A comprehensive understanding of the biology of MIP morphology is vital for therapeutic interventions.